Firms and System Competitiveness in Italy - Alessandro Viviani (Firenze University Press, 2009)
Recent evolution of the Italian industrial system shows how the concepts of localization/delocalization of economic production processes have very little to do with geographical and administrative borders. In this context, a very important and discussed element of complexity is represented by the evaluation of competitiveness. Problems regarding the concept and its proper measurement require a deep elaboration and regard the context of analysis, the information and the available statistical data sources. This book aims at discussing this complex phenomenon from a critical viewpoint both at a macro (economic systems) and at a micro (firms) level showing that they are intrinsically integrated.
Keywords: Economia; Statistica